Fluorescence polarization assays to measure interactions between Gα subunits of heterotrimeric G proteins and regulatory motifs - Maziarz, Marcin (Methods Cell Biol, 2017)
Fluorescence polarization (FP) is a simple and sensitive method allowing for the quantification of interactions between proteins and fluorescently-tagged small molecules like peptides. Heterotrimeric G proteins are critical signal transducing molecules and their activity is controlled by a complex network of regulatory proteins. Some of these regulators have defined short motifs (<40 amino acids) that are sufficient to bind G proteins and subsequently modulate their activity. For these cases, FP represents a robust and quantitative method to characterize the G protein-regulator interaction. Here we describe FP assays in a 384-well plate format to quantify interactions between Gα subunits of heterotrimeric G proteins and peptides corresponding to the Gα Binding and Activating (GBA) or GoLoco motifs, which are present in some proteins with Guanine nucleotide Exchange (GEF) (e.g., GIV/ Girdin) or Guanine nucleotide Dissociation Inhibitor (GDI) (e.g., RGS12) activity, respectively. This assay can be used to determine equilibrium dissociation constants, characterize the impact of single amino acid point mutations on the Gα-peptide interaction and is suitable for high-throughput screening.